An Analysis of Applying Zoom Cloud Meeting Towards EFL Learning in Pandemic Era Covid-19 - Agus Rahmat; Nurul Fachrunnisa (British : Jurnal Bahasa dan Sastra Inggris, 2021)
The objectives of this research are to find out the students’ perspective, the barriers, the advantages and disadvantages as well as the strategies of applying Zoom Cloud Meeting app towards EFL learning of STMIK Handayani in pandemic era Covid-19. The subjects of this research are five students of Manajemen Informatika (MI) and five students of Technical Information Extensive (TI Ext). The research employed descriptive qualitative design by using self-report questionnaire and interview as the research instruments. The result of research showed that (1) the existence of zoom cloud meeting in EFL learning are very effective to stop the spreading of covid 19 in pandemic era but the learning process cannot be perfect than the conventional learning (2) the main barriers of applying zoom cloud meeting are the bad network and the usage of big quota. (3) The advantages are many kinds of good features and high quality access, more flexible, comfortable, and relaxed and disadvantages are the learning condition cannot be felt, the learning is not perfect, make the students lazier and less of togetherness (4) the effective strategies are the methods must be interactive and the materials have to be delivered directly with audio and visual.